2018
DOI: 10.3390/su10124702
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cultural Sustainability of Private Healthcare Providers in an Indian Slum Setting: A Bottom-of-the-Pyramid Perspective

Abstract: Delivery of affordable healthcare services to communities is a necessary precondition to poverty alleviation. Co-creation approaches to the development of business models in the healthcare industry proved particularly suitable for improving the health-seeking behavior of BOP patients. However, scant research was conducted to understand BOP consumers’ decision-making process leading to specific healthcare choices in slum settings, and the relative balance of socio-cultural and socio-economic factors underpinnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The respondents were selected with a stratified purposeful sampling technique, to ensure a theoretically representative sample in terms of gender, age, religion, place of origin and linguistic/cultural variation. In each subgroup, a saturation approach was adopted to ensure appropriate sample size, and respondents were recruited until information redundancy occurred (Angeli et al …”
Section: Methodsmentioning
confidence: 99%
“…The respondents were selected with a stratified purposeful sampling technique, to ensure a theoretically representative sample in terms of gender, age, religion, place of origin and linguistic/cultural variation. In each subgroup, a saturation approach was adopted to ensure appropriate sample size, and respondents were recruited until information redundancy occurred (Angeli et al …”
Section: Methodsmentioning
confidence: 99%
“…About 15 per cent of the 1.3bn population in India has a health insurance coverage and outof-pocket health expenditure is high at 69 per cent of total healthcare expenditure (Chatterjee et al, 2018). Indian consumers in the BoP category spend about 3 per cent of their household expenditure on healthcare and 76 per cent of this amount is for medicines (Angeli et al, 2018). It is necessary to provide a healthcare framework that can address the healthcare needs and health financing needs of the BoP category supported by technological innovations (Matsumoto, 2018).…”
Section: Social Health Insurance In Indiamentioning
confidence: 99%
“…30 Non-kin associates These refer to persons connected to an individual through friendship ties, engagement in similar activities or physical proximity. We found three groups under this category: friends, 34 35 neighbours [36][37][38][39] and colleagues. 30 35 Neighbours in shared structures were sometimes consulted or volunteered health advice when they noticed unusual symptoms in others.…”
Section: Kin Networkmentioning
confidence: 92%
“…33 Influence positive attitudes towards formal health providers Social networks' influence in encouraging positive attitudes towards formal health providers was discussed in one study. 39 The study explored the decision-making behaviours of bottom-of-the pyramid patients (individuals with comparatively weaker earnings) and found that some patients chose and committed to healthcare providers recommended by their family members and neighbours as trustworthy. This was particularly useful as there was a general attitude of mistrust and uncertainties about formal healthcare services.…”
Section: Positive Consequencesmentioning
confidence: 99%